EXPLORING THE EDUCATIONAL IMPACT: A STUDY ON ACCOUNTING STUDENTS’ LEARNING AND DEVELOPMENT DURING INTERNSHIP - Nik Zam Nik Wan; Syuhaila Razak; Suzana San; Siti Nor Adawiah Hussin; Azilawati Abdullah @ Abd Aziz; Noraida Saidi, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Internships are pivotal in bridging the gap between academic learning and real-world application, offering students invaluable experiential learning and professional development opportunities. This research study explores the educational impact of internship periods, focusing on participating students' learning outcomes and experiences. Drawing on a qualitative research approach, data were obtained from student internship reports and were analysed using NVivo software. The findings reveal multifaceted learning experiences encompassing the application of accounting education knowledge, technical skills acquisition, soft skills development, industry knowledge, problem-solving abilities, and teamwork dynamics. Through thematic analysis, key themes emerged, shedding light on the transformative nature of internship experiences and their profound influence on students' personal and professional growth. The implications of these findings for educational institutions, internship programs, and policymakers are discussed, alongside recommendations for enhancing internship experiences and optimizing learning outcomes. This study contributes to the literature on internships and offers insights into effective strategies for integrating experiential learning opportunities within higher education curricula.